Associations between modifiable risk factors and cognitive function in middle-aged and older Chinese adults: joint modelling of longitudinal and survival data - Ran, Qin; Yang, Fang; Su, Qin; Li, Peng; Hu, Yaoyue (Frontiers in Public Health, 2024)
BackgroundStronger associations between modifiable risk factors and cognitive function have been found in younger than older adults. This age pattern may be subject to mortality selection and non-ignorable missingness caused by dropouts due to death, but this remains unclear.MethodsLongitudinal data from 9,562 adults aged 50 and older from Waves 1–4 (2011–2018) of the China Health and Retirement Longitudinal Study were used. Cognitive function was assessed repeatedly using a battery of cognitive tests. Joint models of longitudinal and survival data were applied to examine the associations of modifiable risk factors with cognitive function and mortality.ResultsWorse cognitive function score was associated with being female (coefficient[β] = −1.669, 95% confidence interval [CI]: −1.830, −1.511, p < 0.001), low education (β = −2.672, 95%CI: −2.813, −2.530, p < 0.001), rural residence (β = −1.204, 95%CI: −1.329, −1.074, p < 0.001), stroke (β = −0.451, 95%CI: −0.857, −0.051, p = 0.030), probable depression (β = −1.084, 95%CI: −1.226, −0.941, p < 0.001), and current smoking (β = −0.284, 95%CI: −0.437, −0.133, p < 0.001); whereas dyslipidaemia (β = 0.415, 95% CI: 0.207, 0.626, p < 0.001), heart disease (β = 0.513, 95% CI: 0.328, 0.698, p < 0.001), overweight (β = 0.365, 95% CI: 0.224, 0.506, p < 0.001) and obesity (β = 0.264, 95% CI: 0.048, 0.473, p = 0.014) were associated with better cognitive function. These associations changed less than 5% when the longitudinal and survival data were modelled separately. An increase in cognitive function over age was associated with reduced mortality risk (hazard ratio: 0.418, 95%CI: 0.333, 0.537, p < 0.001). The association between socioeconomic disadvantage and cognitive function was more evident in women than in men, while the associations of socioeconomic disadvantage and lifestyle with cognitive function increased with age.ConclusionMortality selection and non-ignorable missingness caused by dropouts due to death played a minor role in the associations between modifiable risk factors and cognitive function in middle-aged and older Chinese adults.